2018
DOI: 10.1080/15374416.2018.1453365
|View full text |Cite
|
Sign up to set email alerts
|

Parental Expressed Emotion-Criticism and Neural Markers of Sustained Attention to Emotional Faces in Children

Abstract: There is growing evidence for the role of environmental influences on children's information-processing biases for affectively salient stimuli. The goal of this study was to extend this research by examining the relation between parental criticism (expressed emotion-criticism, or EE-Crit) and children's processing of facial displays of emotion. Specifically, we examined the relation between EE-Crit and children's sensitivity in detecting facial displays of emotion. We also examined a neural marker of sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
(77 reference statements)
1
9
0
1
Order By: Relevance
“…Most studies employed an explicit task design, with the exception of Kujawa et al (2012a , 2012b ) and Simonetti et al (2019) . Generally, adult stimuli were used in the FEP task, although James et al (2018) and Woody et al (2019) included morphed child stimuli. The majority of studies included children aged seven years or older, with no studies including children under 5 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies employed an explicit task design, with the exception of Kujawa et al (2012a , 2012b ) and Simonetti et al (2019) . Generally, adult stimuli were used in the FEP task, although James et al (2018) and Woody et al (2019) included morphed child stimuli. The majority of studies included children aged seven years or older, with no studies including children under 5 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a larger N170 amplitude to angry faces was found in healthy adults who experienced childhood abuse and neglect than non-maltreated controls (Fang et al, 2019 ); the P3b amplitude to angry faces was larger in physically abused children than non-abused children (Shackman et al, 2007 ). On the contrary, James et al ( 2018 ) found that children who received high levels of emotional criticism exhibited smaller LPP to all facial expressions (fearful, happy, and sad) than children who received low levels of emotional criticism from their parents, which they explained that children of critical parents may exhibit avoidance of salient facial stimuli. These mixed results might be due to the different types of maltreatment and different age groups (children vs. adults).…”
Section: Introductionmentioning
confidence: 95%
“…Children whose parents express high levels of positive emotions tend to show high levels of social abilities, adaptive skills, social-emotional understanding, and empathy (e.g., Eisenberg et al, 2003;Knafo & Plomin, 2006;Moller et al, 2019;Roth & Assor, 2010). Yet, children of critical and/or harsh parents tend to be less attentive to social interpersonal cues (Cruz-Alaniz et al, 2018;James et al, 2018). Also, frequency of parent-child joint activities predicts preschoolers' social (e.g., Galboda-Liyanage et al, 2003) and academic achievements (e.g., Bingham et al, 2017).…”
Section: The Parenting Pentagon Model (Ppm)mentioning
confidence: 99%